Design of multi-scale textured surfaces for unconventional liquid harnessing. (March 2021) - Tang, Xin; Tian, Ye; Tian, Xiaowei; Li, Wei; Han, Xing; Kong, Tiantian; Wang, Liqiu
Graphical abstract: Abstract: The ability to manipulate liquids in a loss-free and refined manner has long been anticipated, with applications in fields such as analytical chemistry, medical diagnosis, and droplet-based manufacturing. The challenge derives from the liquid/solid contacts, which incur spontaneous spreading, strong pinning, and substantial retention. The retention-proof interfaces, including superhydrophobic surfaces, lubricant-infused surfaces, and liquid marbles, mitigate these issues by respectively introducing air, lubricant, and particulate layers to isolate liquids from underlying solids. Assisted by these interfaces, contrastive physical/chemical designs and engineering methods are leveraged to unlock unparalleled liquid-control methods that are otherwise inaccessible. In this review, we focus on the application of retention-proof interfaces in three facets of manipulation: the aliquoting, grip, and transport of fluids. We discuss the key features, strategies and implementations, highlighting the fundamental physics and operation principles. For aliquoting, the cooperation between diminutive geometries and interfaces in partition droplets are examined. For the grip, we discuss the impact of micro-/nanotextures on adhesion behavior and highlight the mechanisms of switching the adhesive forces. For the transport, we review various engineering and functionalizing forms through which subtle driving forces are dexterously imposed on mobile droplets. The performance of different techniques is evaluated, and potential directions are proposed.